2008
DOI: 10.3201/eid1404.071016
|View full text |Cite
|
Sign up to set email alerts
|

Wild Ducks as Long-Distance Vectors of Highly Pathogenic Avian Influenza Virus (H5N1)

Abstract: Wild birds have been implicated in the expansion of highly pathogenic avian infl uenza virus (H5N1) outbreaks across Asia, the Middle East, Europe, and Africa (in addition to traditional transmission by infected poultry, contaminated equipment, and people). Such a role would require wild birds to excrete virus in the absence of debilitating disease. By experimentally infecting wild ducks, we found that tufted ducks, Eurasian pochards, and mallards excreted significantly more virus than common teals, Eurasian w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
429
9
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(473 citation statements)
references
References 24 publications
32
429
9
3
Order By: Relevance
“…Recently reported experimental infections of six species of wild duck, including mallards, with A/turkey/Turkey/1/2005 (H5N1) virus, showed age‐related observations consistent with those obtained in the present study 26 . In this wild bird study, mallards ( Anas platyrhynchos ) were 8–11 months old and showed ‘abundant virus excretion without clinical or pathologic evidence of debilitating disease’ 26 . Similarly, no clinical or pathological evidence of debilitating disease was observed in 12 wo Pekin ducks in the present study, but ‘abundant excretion’ levels were not observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently reported experimental infections of six species of wild duck, including mallards, with A/turkey/Turkey/1/2005 (H5N1) virus, showed age‐related observations consistent with those obtained in the present study 26 . In this wild bird study, mallards ( Anas platyrhynchos ) were 8–11 months old and showed ‘abundant virus excretion without clinical or pathologic evidence of debilitating disease’ 26 . Similarly, no clinical or pathological evidence of debilitating disease was observed in 12 wo Pekin ducks in the present study, but ‘abundant excretion’ levels were not observed.…”
Section: Discussionsupporting
confidence: 92%
“…This association also coincided with the appearance of clinical signs and mortality. Recently reported experimental infections of six species of wild duck, including mallards, with A/turkey/Turkey/1/2005 (H5N1) virus, showed age‐related observations consistent with those obtained in the present study 26 . In this wild bird study, mallards ( Anas platyrhynchos ) were 8–11 months old and showed ‘abundant virus excretion without clinical or pathologic evidence of debilitating disease’ 26 .…”
Section: Discussionsupporting
confidence: 90%
“…House sparrows that were examined histopathologically had viral antigen in neurons of the central and peripheral nervous system, but generally the extent was greatly reduced compared with other wild avian species that have been experimentally infected with H5N1 HPAI viruses. 3,4,12 Based on the very low BID 50 and BLD 50 of the A/ whooper swan/Mongolia/244/05 virus for house sparrows, it would seem likely that bird-to-bird transmission within this species could occur, and it is unknown why transmission of H5N1 HPAI virus between co-housed sparrows in previous experimental trials was unsuccessful. 2 Although this suggests a low probability of intraspecific transmission, additional studies are warranted to further investigate potential H5N1 HPAI virus transmission between sparrows, particularly as multiple genotypes of H5N1 HPAI virus have been isolated from terrestrial birds.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Viral transmission between migratory waterfowl and domestic bird populations, in either direction, can occur through several mechanisms, including direct contact in areas where the 2 groups share environments, scavenging on H5N1 HPAI virus-infected carcasses, and through ''bridge'' species that can transmit the virus between domestic poultry and migratory waterfowl populations. Small terrestrial birds commonly found around poultry environments have a strong potential to serve as important ''bridge'' species owing to their peridomestic behavior and extensive interaction with both free-living and domesticated avian populations.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, wild species of ducks, geese and swans have shown the ability to replicate and shed H5N1 for several days without showing clinical or pathologic signs of disease (Kim et al, 2009). Among the species studied, mallards (Anas platyrhynchos), mute swans (Cygnus olor), cackling geese (Branta hutchinsii), and bar-headed geese (Anser indicus) pose a greater risk for HPAI H5N1 transmission (Brown et al, 2006(Brown et al, , 2008aKeawcharoen et al, 2008). Some wild birds may be partially immune to HPAI H5N1 due to previous exposure to LPAI viruses (Seo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%